(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The world witnessed an epidemic and healthcare workers played a vital role. They played a key role in providing essential health services and distributing COVID-19 vaccines along with balancing the additional service requirements. In their endeavors to protect the larger group, they ran a higher chance of being infected and were subjected to various dangers, including psychological discomfort, exhaustion, stigma, and many others. Also, the data related to healthcare workers and the risks of taking care of patients is insufficient. Hence, it is imperative to examine and study elevated risk because of COVID-19 among healthcare workers to avert further spread. The author of this paper attempts to study the correlation of exposure risk with infection while treating the patient. A detailed study was conducted to assess the risks associated with getting exposed to COVID-19 among healthcare workers in Mumbai city and data were collected through a questionnaire that was framed for collating information on socio-demographic factors as well as exposure-related. The assessment of the risk related to disease because of exposure was done and the data was examined using the SPSS tool.A total of 209 healthcare workers were studied, out of which 16 (7.6%) tested positive for COVID-19. The result states that the factors related to exposure had no correlation to patients who tested positive. While in the risk category, the high exposure was showing strong relation with a positive test of COVID-19. The respondents with risk of high category were more frequent to get infected. It was needed to educate and train them at different levels in the hospitals to find out standard practices in order to prevent COVID-19 among healthcare providers. Along with that, designing appropriate preventive measures to reduce the exposure risk at all levels among healthcare sectors also a must.